Pengaruh iklim sekolah dan pola komunikasi terhadap profil pelajar pancasila di sekolah dasar - Azzahro, Tsabita Fuadina; Marmoah, Sri; Budiharto, Tri (Universitas Sebelas Maret, 2025)
The purpose of this study was to determine the extent of the influence of aspects of school climate and communication patterns in school culture on the profile of Pancasila students in public elementary schools throughout the Slamet Riyadi Laweyan Surakarta Cluster. This study uses a quantitative correlation approach with multiple linear regression analysis. The data sources in this study were students of SDN Mangkubumen Lor No. 15 and SDN Mangkubumen Kidul No. 16. The data collection technique was carried out using a questionnaire. The data analysis used was multiple linear regression analysis. Multiple linear regression analysis can produce calculations of t-test, F-test, and coefficient of determination. The results of this study indicate that aspects of school climate and communication patterns in elementary schools throughout the Slamet Riyadi Laweyan Surakarta Cluster in the 2023/2024 academic year have a significant influence of 0.608 or 60.8% on the profile of Pancasila students. The implementation of the Pancasila student profile can be done through school culture, Pancasila student profile strengthening projects, intracurricular and extracurricular activities, therefore it is recommended to research the implementation of the Pancasila student profile through other activities.